2001
DOI: 10.4049/jimmunol.166.5.2982
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and Effector CD4 T Cells in Nonobese Diabetic Mice Recognize Overlapping Determinants on Glutamic Acid Decarboxylase and Use DistinctGenes

Abstract: The 524–543 region of glutamic acid decarboxylase (GAD65), GAD65(524–543), is one of the first fragments of this islet Ag to induce proliferative T cell responses in the nonobese diabetic (NOD) mouse model of spontaneous autoimmune diabetes. Furthermore, NOD mice given tolerogenic doses of GAD65(524–543) are protected from spontaneous and cyclophosphamide-induced diabetes. In this study, we report that there are at least two I-Ag7-restricted determinants present in the GAD65(524–543) sequence, each capable of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 33 publications
4
60
1
Order By: Relevance
“…The sequence of p524-543 is SRLSKVAPVIKARMMEYGTT, and the only acidic residue, E539, is unlikely to function as a P9 anchor with the bulky R536 in P6. We previously set forth a hypothesis of two-registers to explain the distinction between the N-and C-terminal peptides, p524-538 and p530-543 [23]. Peptide p524-538 could bind to I-A g7 using I533 and R536 as anchors for the P6 and P9 pockets, whereas for the peptide p530-543, M537 and Y540 were likely to be anchors binding to the P6 and P9 pockets, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sequence of p524-543 is SRLSKVAPVIKARMMEYGTT, and the only acidic residue, E539, is unlikely to function as a P9 anchor with the bulky R536 in P6. We previously set forth a hypothesis of two-registers to explain the distinction between the N-and C-terminal peptides, p524-538 and p530-543 [23]. Peptide p524-538 could bind to I-A g7 using I533 and R536 as anchors for the P6 and P9 pockets, whereas for the peptide p530-543, M537 and Y540 were likely to be anchors binding to the P6 and P9 pockets, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that T cells recognizing the N-terminal p524 peptide use BV12 TCR very frequently and T cells specific for the C-terminal p530 peptide are largely BV4 [23]. In fact, we found that three out of the five p524-538-specific hybridoma clones that we generated, including 524.59.3 and 524.169.17, used BV12 TCR, whereas, all four p530-543-specific clones, including 530.45.19 and 530.97.3, were BV4.…”
Section: The Nod T Cell Repertoire Is Highly Focused and Frequently Umentioning
confidence: 99%
See 2 more Smart Citations
“…However, unlike MOGreactive T cell clones, not all of the PLP-reactive clones needed the same nonameric core epitope for their stimulation [35]. In other studies describing T cells reactive against MBP89-101 in SJL/J mice [36,37], against antigens/epitopes in rheumatoid arthritis (such as collagen II [38][39][40]) or against antigens/epitopes in type I diabetes (such as insulin [41,42] or glutamic acid decarboxylase 65 [43,44]), both restricted and highly diverse TCR repertoires have been reported to be associated with reactivity to the disease-relevant antigen/epitope. However, in the studies where diverse TCR expression for recognition of the epitopic region was demonstrated, the nonameric core sequence essential for stimulation of the heterogeneous T cells was not assigned [40,41].…”
Section: Discussionmentioning
confidence: 99%